Targeting cellular mitophagy as a strategy for human cancers - Dong, Yuming; Zhang, Xue (Frontiers in Cell and Developmental Biology, 2024)
Mitophagy is the cellular process to selectively eliminate dysfunctional mitochondria, governing the number and quality of mitochondria. Dysregulation of mitophagy may lead to the accumulation of damaged mitochondria, which plays an important role in the initiation and development of tumors. Mitophagy includes ubiquitin-dependent pathways mediated by PINK1/Parkin and non-ubiquitin dependent pathways mediated by mitochondrial autophagic receptors including NIX, BNIP3, and FUNDC1. Cellular mitophagy widely participates in multiple cellular process including metabolic reprogramming, anti-tumor immunity, ferroptosis, as well as the interaction between tumor cells and tumor-microenvironment. And cellular mitophagy also regulates tumor proliferation and metastasis, stemness, chemoresistance, resistance to targeted therapy and radiotherapy. In this review, we summarized the underlying molecular mechanisms of mitophagy and discussed the complex role of mitophagy in diverse contexts of tumors, indicating it as a promising target in the mitophagy-related anti-tumor therapy.